Memcapacitor emulator based on the Miller effect. (19th February 2019) - Romero, Francisco J.; Morales, Diego P.; Godoy, Andres; Ruiz, Francisco G.; Tienda‐Luna, Isabel M.; Ohata, Akiko; Rodriguez, Noel
Summary: This work provides the guidelines to design and implement an elemental memcapacitor circuit emulator based on the relation between memcapacitance and the Miller effect in voltage amplifiers. The emulator is presented theoretically in a top‐down approach, from the circuit behavior to the foundations of the constitutive equations of the memcapacitance and the electrical mutation of a memristor. Then, a practical and simple circuit implementation is demonstrated by SPICE computer simulations, circumventing the solid‐state memristor by a two‐state flux‐dependent resistor, which modulates the gain of the amplifier in consonance to the flux of the input signal. Further electrical properties of the system are extracted from its physical implementation in a field‐programmable analog array. The work is concluded illustrating the functionality of the memcapacitor emulator to study neuromorphic applications with a long‐term potentiation example. Abstract : In this work, the Miller effect has been suited as a simple approach to build memcapacitor emulators from the electrical mutation of a memristor. The emulator is presented theoretically, and thereafter, its feasibility is demonstrated by SPICE simulations as well as its physical implementation in a field‐programmable analog array. Finally, the work is concluded illustrating the functionality of the memcapacitor emulator to study neuromorphic applications.